Analysis of complex survival data subject to semi-competing risks - Peng, Mengjiao (2019)
This thesis is devoted to develop novel methods for the analysis of complex survival data subject to semi-competing risks. In many clinical trials, multiple time-to-event endpoints, including the primary endpoint (e.g., time to death) and secondary endpoints (e.g. progression-related endpoints) are commonly used to determine treatment efficacy. These endpoints are often biologically related. One secondary endpoint and one primary endpoint often arise in medical research and form semi-competing risks where the observation of the secondary endpoint will be censored by the primary endpoint when it occurs earlier than the secondary endpoint, but not vice versa. There has been a longstanding research interest in the analysis of semi-competing risks data.